THE INFLUENCE OF WORK ENVIRONMENT AND COMPENSATION ON EMPLOYEE TURNOVER INTENTION - Ady Sumadi Anwar; Wahyu Anugrah Manippi; Kamaluddin R (ITB AAS Indonesia Surakarta, 2024)
Abstract The persistence of a employee in a company is an indication that the company can be said to be a successful company because employees are the lifeblood of the company and without employees the company cannot do anything. There are a number of factors that can determine whether an employee will stay or not, one of which is the work environment. This research aims to examine the influence of the work environment on Employee Turnover Intention. Different from other studies, this research adds the Compensation variable as an Independent variable which researchers believe can influence the Employee Turnover Intention variable. This research is a quantitative research with an exploratory approach which was distributed using the questionnaire method to 300 Basmlalah supermarket employees spread throughout Indonesia. The data collected was analyzed using smart PLS 3.0. The research results show that the Work Environment variable has a negative relationship and an insignificant influence on the Employee Turnover Intention variable because the t-table value is negative and above the significance level. On the other hand, according to the researcher's assumption that the Compensation variable has a positive relationship and has a significant influence on the Employee Turnover Intention variable because the t-table value is positive and below the significance level. Thus, the first hypothesis is rejected and the second hypothesis is accepted. Keywords : Work Environment, Compensation, Employee Turnover Intention